Functional and clinical significance of SALL4 in breast cancer - AKKİPRİK, MUSTAFA (SAGE PUBLICATIONS LTD, 2016)
The gene encoding Sal-like 4 (Drosophila) (SALL4) is a zinc-finger transcriptional factor and a vertebrate orthologous of the Drosophila gene spalt (sal), which is upregulated in some cancers. SALL4 is expressed in the early developmental stages of Drosophila. Moreover, murine SALL4 plays a vital role in protecting the properties of embryonic stem (ES) cells and guiding the outcome of the primal inner cell mass by interacting with OCT4 and NANOG. SALL4 in ES cells and tumor cells is known as a regulator for controlling cell growth, proliferation, and apoptosis. However, the downstream goals of SALL4 remain largely uncharted. SALL4 expression has been detected in various cancers, including a subset (30 %) of solid tumors, such as breast cancer (BCa), ovarian cancer, gastric cancer, Wilms tumor, and germ cell tumors. A study has reported that SALL4 expression is commonly upregulated in human breast tumors (similar to 86 %) and that overregulation of this gene is often linked to tumor progression. In this review, we provide an overview concerning the role of SALL4 in BCa development and progression. Furthermore, this review may identify some drugs/inhibitors for the development of BCa-specific therapies by targeting SALL4. In the future, SALL4 may be a new biomarker as a diagnostic/therapeutic target of BCa, which would be a new direction in targeted BCa therapy. To our knowledge, this is the first review of the role of SALL4 in BCa development and progression.
Keywords: SALL4; Breast cancer; ES cells; Therapy; OCT4; NANOG; GERM-CELL TUMORS; TRANSCRIPTION FACTOR SALL4; ACUTE MYELOID-LEUKEMIA; EARLY EMBRYONIC-DEVELOPMENT; MALIGNANT RHABDOID TUMORS; RENAL-OCULAR SYNDROME; RADIAL RAY SYNDROME; YOLK-SAC TUMORS; OKIHIRO-SYNDROME; HEPATOCELLULAR-CARCINOMA